Preliminarna raziskava merskih značilnosti Vprašalnika o odnosih s starši (VOS) - Kozina, Ana (Psihološka obzorja (Ljubljana), 2010)
The purpose of the article is to introduce the Children-parents relationship questionnaire (VOS) and to present its metric characteristics. The questionnaire is based on parental styles of D. Baumrind (1967) and 3D model of parental styles developed by Milivojević and others (2004). The questionnaire was developed under assumption that relationship between children and their parents influences educational achievement of children. Results on convenience sample (N = 333) of seventh, eighth and ninth grade students in Slovenia show a three dimensional structure of the questionnaire: (a) authoritative parental style and autonomy, (b) authoritarian parental style and (c) rewarding. Questionnaires f reliability in terms of internal consistency (,72 > f < ,95) as well as sensitivity (raverage=,67) proved to be sufficient. Our results show significant gender differences in perceived authoritative parental style and autonomy as well as low association between school grades and the perceived relationship.
Keywords: vzgojni stili; učni uspeh; odnosi; starši; child; otroci; vprašalniki; psihometrične značilnosti